The role of cardiovascular imaging for myocardial injury in hospitalized COVID-19 patients - Cosyns, Bernard (Eur Heart J Cardiovasc Imaging, 2020)
Recent EACVI recommendations described the importance of limiting cardiovascular imaging during the COVID-19 pandemic in order to reduce virus transmission, protect healthcare professionals from contamination, and reduce consumption of personal protective equipment. However, an elevated troponin remains a frequent request for cardiac imaging in COVID-19 patients, partly because it signifies cardiac injury due to a variety of causes and partly because it is known to convey a worse prognosis. The present paper aims to provide guidance to clinicians regarding the appropriateness of cardiac imaging in the context of troponin elevation and myocardial injury, how best to decipher the mechanism of myocardial injury, and how to guide patient management.